(untitled) (Journal Of Educational and Psychological Researches, 2015)
This study aimed to identify the attitudes of school teachers and principals at basic government schools in Ajloun governorate towards the inclusion of disabled students at basic schools, and investigate how they will accept the merger. To achieve the purpose of this study, a questionnaire containing 35 items was administered to school teachers and principals to measure their attitudes toward the inclusion of disabled students in regular schools. The sample of this study consisted of 43 male teachers and (74) female teachers and principals. The frequency, normal distribution, arithmetic means and t-test were used to analyze the data of present study. The findings showed that there were a statistically significant differences in the attitudes of regular government school teachers and principals due to gender variable in favor of males. The findings also showed a statistically significant differences in attitudes due to the profession variable in favor of school principals. However, the findings of this study showed no statistically significant differences in the attitudes due to certain variables such as years of experience, academic qualification and specialization.